2010
DOI: 10.1021/es1021944
|View full text |Cite
|
Sign up to set email alerts
|

Wet Oxidation of Salicylic Acid Solutions

Abstract: Salicylic acid is a frequent pollutant in several industrial wastewaters. Uncatalyzed wet air oxidation, which is a promising technique for the treatment of phenolic effluents, has not been analyzed yet for the removal of salicylic acid. The effect of different conditions of pH (1.3-12.3), pressure (1.0-4.1 MPa), temperature (413-443 K), and initial concentrations (1.45-14.50 mM) on the wet oxidation of salicylate/salicylic acid solutions have here been investigated. The pH value of the reaction media was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This observation was supported by the fact that the toxicity originated from the remaining DEP and the oxidation products accumulating as the reaction progressed. Toxicity tests on the effects of associated intermediate products to Photobacterium phosphoreum have been reported in previous studies (37). The EC50 (i.e., concentration for 50% maximal effect) followed the sequence, acetic acid (2.17 mM) > ethyl 2-hydroxybenzoate (1.55 mM), which explains that the toxicity effect of intermediate products in the mineralization process was different.…”
Section: Toxicity Evolvementmentioning
confidence: 77%
“…This observation was supported by the fact that the toxicity originated from the remaining DEP and the oxidation products accumulating as the reaction progressed. Toxicity tests on the effects of associated intermediate products to Photobacterium phosphoreum have been reported in previous studies (37). The EC50 (i.e., concentration for 50% maximal effect) followed the sequence, acetic acid (2.17 mM) > ethyl 2-hydroxybenzoate (1.55 mM), which explains that the toxicity effect of intermediate products in the mineralization process was different.…”
Section: Toxicity Evolvementmentioning
confidence: 77%
“…This small amount of phenol indicates that excess OH radical decomposed phenol as soon as it was generated. The mechanism of degradation by the radicals was proposed by Collado et al 30 They reported that salicylic acid is first converted to phenol, followed by further conversion to hydroquinone or catechol.…”
Section: ¹1mentioning
confidence: 99%
“…and also it is used as a raw material. This contaminant has to be removed from the wastewater and spreading in environment should be avoided [5,6]. Heterogeneous photocatalytic oxidation is one of the promising processes among the AOP which is successfully employed for degradation of various OC.…”
Section: Introductionmentioning
confidence: 99%